Proposed Auto Feeder Conveyor Project Scheduling Using the Critical Path Method at PT XYZ - Hakim, Luqman; Saputra, Jefri (Jurnal IPTEK, 2024)
Scheduling is important and must be done in every project implementation. PT XYZ is a company engaged in the production of industrial machine fabrication. One of the jobs PT XYZ obtained was making auto feeder conveyors. In its scheduling plan, PT XYZ estimates that the work will be completed within 37 days. However, in practice, the work was completed within 42 days. There was a delay of 5 days. This delay will cause losses in costs and also cause consumer dissatisfaction. To resolve this delay, the critical path method (CPM) is used. After using the CPM method, the auto feeder conveyor manufacturing project can be completed within 39 days. The critical path of the project lies in work B – E – F – G – H – I – J.